Challenges in recycling used cooking oil to produce biodiesel in Polokwane - Ramuedzisi, Humbelani Elson (My University, 2016)
In response to the ever increasing problems associated with climate change, and greenhouse gas emissions, many countries in the world are developing and adopting climate change resilient policies that support green economy. Green economy sector in South Africa has not as yet received much expected attention as a key sector to address economic and environmental problems. The use and the production of renewable fuels, such as biodiesel are known to have significant economic and environmental benefits. However, progress in the production of biodiesel is hampered by limits imposed by government on the use of fresh vegetable extracted oils for production of biodiesel, mainly due to challenges on food security; and the impact this will have on food prices. In recent years recycling has become an important tool to address waste problems; pollution control; and socio-economic problems such as joblessness, poverty and social inequity. Used cooking oil has always been considered waste and an environmental burden. Therefore through technology advancement of recycling, wastes such as used cooking oil have become useful resources for biodiesel production. This research is about the challenges in recycling used cooking oil to produce biodiesel. The study recommended that in order to address challenges facing sustainability of our environment, and high unemployment rate; small recycling industries such as those operating in Polokwane will need government support such as biodiesel sector policies and regulations, to encourage investment in the biodiesel value chains in a way that will lead to the achievement of green economy goals.
Thesis submitted in 50 % completion of the degree of Master of Management in the field of Public and Development Management at the University of the Witwatersrand, Johannesburg. 20 June 2016
Keywords: Recycling (Waste, etc.)--South Africa.; Biodiesel fuels; Vegetable oils as fuel